PENYEBAB TERJADINYA POLITIK UANG - Mahroza, Dekki (Ilmu dan Budaya, 2024)
Money politics during election campaigns has become increasingly massive in the post-1998 Reformation era. The practice of money politics reflects the process of decline in democratic development in Indonesia. Money politics is caused by various factors, including politic, economic, legal, and culture. This article analyzes descriptively the causes of the of money politics which are caused by political economy, legal and cultural factors. This research is a multidisciplinary research using a qualitative approach applied using a literature study method consisting of books, journals, and newspaper articles related to the author's research. The results of this study indicate that unfair economic development, weak law enforcement, and the continued strength of the patron-client culture are non-political factors causing money politics in Indonesia. The suggestion from the results of this study is that community empowerment carried out by various elements of civil society, whether in the form of political education, economic empowerment of citizens, and building relationships with prospective leaders during the campaign period based on legally binding political contracts, is a strategic effort to combat the massive money politics that occurs in society.   Abstrak   Politik uang pada saat masa kampanye pemilu menjadi semakin massif di era pasca Reformasi 1998. Praktek politik uang mencerminkan proses kemunduran pembangunan demokrasi di Indonesia. Politik uang disebabkan berbagai faktor baik itu politik, sosial, ekonomi, hukum, dan budaya. Tulisan ini menganalisa secara deskriptif penyebab terjadinya politik uang yang disebabkan oleh faktor ekonomi politik, hukum, dan budaya. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode studi pustaka yang terdiri dari buku-buku, jurnal, dan artikel koran yang terkait dengan penelitian penulis. Hasil dari penelitian ini menunjukkan bahwa ketidakadilan pembangunan ekonomi, lemahnya penegakan hukum, dan masih kuatnya budaya patron-klien adalah faktor-faktor non-politik penyebab terjadinya politik uang di Indonesia. Saran dari hasil penelitian ini adalah, pemberdayaan masyarakat yang dilakukan berbagai elemen civil society baik itu dalam bentuk pendidikan politik, pemberdayaan ekonomi warga, dan membangun hubungan dengan calon pemimpin di masa kampanye berdasarkan kontrak politik yang terikat hukum merupakan upaya strategis untuk melawan massifnya politik uang yang terjadi di masyarakat.